2003
DOI: 10.5694/j.1326-5377.2003.tb05496.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ototopical antibiotics for chronic suppurative otitis media in Aboriginal children: a community‐based, multicentre, double‐blind randomised controlled trial

Abstract: Objectives: To compare the effectiveness of ototopical ciprofloxacin (0.3%; CIP) with framycetin (0.5%), gramicidin, dexamethasone (FGD) eardrops (5 drops twice daily for 9 days) together with povidone‐iodine (0.5%) ear cleaning as treatments for chronic suppurative otitis media (CSOM) in Aboriginal children. Design and participants: Aboriginal community‐controlled, community‐based, multicentre, double‐blind, randomised controlled trial in eight Aboriginal Community Controlled Health Services across northern A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
81
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 25 publications
0
81
1
1
Order By: Relevance
“…While we have demonstrated it is possible to undertake high quality RCTs in Aboriginal primary health care settings [28] the difficulty of enrolling participants in future studies should not be underestimated and needs to be carefully considered in planning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we have demonstrated it is possible to undertake high quality RCTs in Aboriginal primary health care settings [28] the difficulty of enrolling participants in future studies should not be underestimated and needs to be carefully considered in planning.…”
Section: Discussionmentioning
confidence: 99%
“…Individually randomised multicentre drug trials have been demonstrated to be possible in Aboriginal and Torres Strait Islander health [28]. Cluster randomised multicentre trials may be another solution for more complex non-placebo controllable interventions such as BOABS, however the risks of: 1) heterogeneity between sites; 2) the intervention only working in some locations; 3) added complexity of both design and analysis; 4) a substantially larger sample size required to obtain the same statistical power; 5) post-randomisation selection bias if randomisation occurs prior to participant recruitment; and 6) a potential slowdown of recruitment in the clusters that are to receive the less interesting treatment such as “usual care” [29-31], remain.…”
Section: Discussionmentioning
confidence: 99%
“…RCTs provide high-quality research and evidence, and can be undertaken in this setting. In 2002 Kimberley ACCHS took part in a double blind, multi-centre, RCT that was conducted by the National Aboriginal Community Controlled Health Organisation (NACCHO Ear Health Trial) [21]. The research methodology of this RCT placed Aboriginal people in control of their own research [22].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: Chronic suppurative otitis media (CSOM) is a long‐term problem which often has serious effects on hearing, speech and learning. Couzos and colleagues have shown that local treatment with ciprofloxacin (CIP) eardrops clears episodes of purulent discharge more efficiently than the commonly used framycetin, gramicidin and dexamethasone (FGD) eardrops 1 . This hardly ranks as a “cure” as suggested by the authors.…”
mentioning
confidence: 99%